Preparing Teachers in the Era of “Independence Learning” in Indonesia - Jahari, Jaja (International Journal of Psychosocial Rehabilitation, 2020)
: Development of education in the learning process is affected by the phenomena of Industrial 4.0. Education in Indonesia also adjusts to these developments and carries the concept of "Independence Learning". Therefore, the aim of this study is to elaborate and analyse the teacher readiness in facing the era of rapid technological disruption by still instilling quality skills, character, and work ethic. This study uses qualitative approach as methodology with literature review and content analysis in UIN Sunan Gunung Djati Bandung as a case study. This study found that UIN Sunan Gunung Djati Bandung ready to prepare teachers in the era of independence learning in accordance based on technology needs. This finding can be implemented in educational field, especially in higher education.